2021
DOI: 10.3390/ani11051197
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Thermal Variability and Behaviour as Bio-Thermal Indicators of Heat Stress in Dairy Cows in a Compost Barn: A Case Study

Abstract: The spatial variability and behavioural aspects of compost-bedded pack barns remain unknown in subtropical regions. In this study, we investigated whether spatial variability occurs in the thermal environment of a compost barn and how the behaviour of dairy cows with different numbers of lactations differs in this system. The spatial sampling design comprised a grid of 108 locations inside the facility. At each location, we measured air temperature, relative humidity, wind speed, and bed temperature at 9:00, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This large increase in publications indicates that the compost barn system has become a topic of global interest. The main topics discussed in that year were spatial variability in the thermal environment and bedding characteristics [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…This large increase in publications indicates that the compost barn system has become a topic of global interest. The main topics discussed in that year were spatial variability in the thermal environment and bedding characteristics [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average dimensions found in the studied CBP barns were 49.1 m long by 21.9 m wide. Other studies reported similar dimensions, such as 24.4 m wide by 31.4 m long [ 21 ] and 20.2 m wide by 43.5 m long [ 22 ]. Moreover, in these studies, the number of animals in the herds was similar to that of our findings.…”
Section: Discussionmentioning
confidence: 71%
“…Reduced areas per animal may concentrate a greater amount of feces and urine in the bed, increasing the moisture content of the bed and making it difficult to manage it. Different bed areas per animal have been reported in the literature, such as 7.4 m 2 ∙cow −1 [ 9 ], 8.6 m 2 ∙cow −1 [ 15 ], 12–17 m 2 ∙cow −1 [ 21 ], 14.6 m 2 ∙cow −1 [ 22 ], 11–19 m 2 ∙cow −1 [ 34 ], and 10.5 m 2 ∙cow −1 [ 38 ]. However, if the bed area is less than 9.3 m 2 ∙cow −1 , the moisture and compaction of the bed may increase [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have carried out the mapping of the thermal environment inside CBP systems, few studies have evaluated this environment under Brazilian winter conditions. The use of this tool in animal ambience is quite satisfactory, and has been carried out by several researchers [ 10 , 11 , 20 , 21 , 22 , 23 , 24 ]. In view of the above, the objective of this study was to evaluate and characterize the dependence and spatial distribution of the thermal environment variables and indices in an open compost-bedded pack barn system with positive-pressure ventilation (CBPPV) during the Brazilian winter period.…”
Section: Introductionmentioning
confidence: 99%